Beyond the Classroom: A Comprehensive Tutoring Model for Higher Education - Landázuri Espinoza, Sandra Nadyedja (2025)
This article aims to propose a comprehensive tutoring model that holistically addresses the needs of university students, considering academic, personal, and psychosocial aspects. The research employed a mixed-methods approach (qualitative and quantitative), utilizing techniques such as focus groups and a pilot test. The focus groups included 16 students from various degree programs, including Accounting, Business Administration, Law, and International Business, as well as 16 faculty members from different disciplines, such as Law, Business Administration, Architecture, Social Communication, Accounting, International Business, and Design. The instruments used consisted of a script with six open-ended questions for the focus groups and students’ academic grades as quantitative data. The proposed model comprises three modalities: academic tutoring, provided by faculty members; mentoring, which focuses on personal and psychosocial aspects; and peer tutoring, where high-achieving students support their peers. During the pilot test, these tutoring modalities were implemented with a group of 60 students from various degree programs and academic levels. Quantitative data were analyzed using SPSS, while qualitative data were processed with ATLAS.ti software. The main findings revealed an improvement in the academic performance of students who participated in the comprehensive tutoring model compared to their previous grades without tutoring. The study concludes that the comprehensive tutoring model is an effective strategy for enhancing university students’ academic performance and preventing course failure. The combination of academic, mentoring, and peer tutoring proved to be a valuable approach to addressing students’ needs and fostering their academic success.